Evaluación del aprovechamiento del uso de subproductos del plátano (Musa paradisiaca) y del maíz (Zea mays) para la crianza del chame (Dormitator latifrons) - Alcívar Villamil, Wilberto Joseph (2022)
The research was carried out at the ESPAM MFL in a period of nine months, its objective was the evaluation of the use of by-products of the banana (Musa paradisiaca) and corn (Zea mays) in the preparation of balanced feed for the breeding of Chame (Dormitator latifrons), the investigation that was divided into three phases: the first phase consisted in the characterization of the current situation of the management of the by-products of the crops in CIIDEA and the Agricultural area through interviews, the second phase consisted in evaluating the growth and fattening of chame (Dormitator latifrons) in the nutritional contribution of pellet-type food made with by-products of plantain (Musa paradisiaca) and corn (Zea mays), which was developed in a simple DCA, consisting of 4 treatments (T1 - 25 % Musa paradisiaca and 75% Zea mays, T2 - 50% Musa paradisiaca and 50% Zea mays, T3 - 75% Musa paradisiaca and 25% Zea mays, treatment 4 consisted of conventional feed For Tilapias, data on the weight and length of the fish were taken every 15 days in order to calculate food consumption, growth rate, fattening rate and mortality. As a final phase, the cost-benefit analysis of the most efficient treatment was carried out and thus obtain the production cost per kilogram of food. According to the interviewees, the corn by-products generated in the cultivation area are: stem, rachis, leaves, and stubble corn, cob, stems, leaves, used in the production of pellet-type food, and through bromatological analysis, it was determined that had excellent properties such as: Proteins, fats, ashes and moisture, the most efficient treatment was T3, where growth and fattening rates were higher than the other treatments. The use of Musa paradisiaca and Zea mays for the preparation of balanced feed is an efficient alternative due to its great nutritional contribution to the chame’s diet, so the development of this type of technology allows adding value to waste and at the same time meets with the conservation of the environment.